The impact of randomized trial results on abdominal aortic aneurysm repair rates from 2003 to 2016: A population-based time-series analysis. (August 2019) - Salata, Konrad; Hussain, Mohamad A; Mestral, Charles de; Greco, Elisa; Mamdani, Muhammad; Tu, Jack V; Forbes, Thomas L; Bhatt, Deepak L; Verma, Subodh; Al-Omran, Mohammed
Abstract: Objectives: The uptake of endovascular aortic repair for elective and ruptured abdominal aortic aneurysm repair is not well studied. We aimed to examine the trends in open surgical repair and endovascular aortic repair of eAAA and rAAA and to examine the effects of randomized trial publications on elective open surgical repair and endovascular aortic repair rates. Methods: We conducted a population-based time-series analysis of eAAA and rAAA repairs in Ontario, Canada from 2003 to 2016. We examined changes in overall and approach-specific rates of eAAA and rAAA repair using exponential smoothing models. Interventional autoregressive integrated moving average models were fit to the eAAA rates to examine the impact of randomized trial results on these rates. Results: We identified 19, 489 eAAA (12, 232 open (63%) and 7257 endovascular (37%)) and 2732 rAAA (2466 open (90%) and 266 endovascular (10%)) repairs from 2003 to 2016. The rate of eAAA repair declined from 6.39/100, 000 in 2003 to 5.59/100, 000 in 2016 (13% decrease, p = 0.17). The rate of elective open surgical repair decreased nearly three-fold from 6.07/100, 000 to 2.12/100, 000 ( p < 0.0001), while elective endovascular aortic repair increased approximately 10-fold (0.32/100, 000 to 3.47/100, 000, p < 0.0001). The rate of ruptured open surgical repair decreased from 1.62/100, 000 to 0.37/100, 000 ( p < 0.44), while ruptured endovascular aortic repair uptake increased (0.00/100, 000 to 0.12/100, 000, p < 0.25). The mid-term results of the DREAM and EVAR-1 trials were associated with a decrease in the rate of elective open surgical repair decline after 2010 ( p = 0.01). Conclusions: While elective open surgical repair use has significantly decreased from 2003 to 2016, elective endovascular aortic repair use has significantly increased. The DREAM and EVAR-1 results significantly impacted the observed rates of elective open surgical repair only. The reasons for these trends require further characterization.